Systematic analysis of the nociceptive blink reflex: reliability and association with psychological factors - Costa, Yuri Martins (2016)
The present study aimed to estimate the reliability of the nociceptive blink reflex (nBR) and to evaluate the possible association between the nBR and various pain-related psychological measures: the Anxiety Sensitivity Index-3 (ASI-3), the Fear of Pain Questionnaire III (FPQ-III), the Pain Vigilance and Awareness Questionnaire (PVAQ), the Somatosensory Amplification Scale (SSAS), the Pain Catastrophizing Scale (PCS) and the Situational Pain Catastrophizing Scale (S-PCS). Twenty-one healthy participants were evaluated in two sessions. The nBR was elicited by a so-called nociceptive-specific electrode placed over the entry zone of the right supraorbital (V1R), infraorbital (V2R) and the mental (V3R) nerve and left infraorbital (V2L) nerve. The outcomes were: (a) individual electrical sensory (I0) and pain thresholds (IP); b) root mean square (RMS), area-under-thecurve (AUC) and onset latencies of R2 responses; and c) stimulus-evoked pain on a 0-10 numerical rating scale. The questionnaires ASI-3, FPQ-III, PVAQ, SSAS, PCS and S-PCS were also applied. Intraclass Correlation Coefficients (ICCs) and Kappa statistics were computed as a measure of the reliability (=5%). Besides, Pearson correlation coefficient was used to associate the average of nBR measurements among all sites and the questionnaires. The significance level was set up after a Bonferroni correction (adjusted =0.8%). ICCs were fair to excellent in 82% of the psychophysical measures and in 86% of V1R, V2R and V2L nBR parameters, whereas the V3R showed poor reliability in 52%. ICCs for intrarater reliability were fair to excellent in 70% of measurements (V3R showed the lowest values) and in 75% of interrater measurements. All kappa values showed at least fair agreement and the majority of the nBR measures (93%) were considered to have moderate to excellent reliability. There was no correlation for any pair of variables considering the adjusted significance level (p>0.008) and only a single significant correlation considering the standard significance level (p < 0.05), where the pain intensity (NRS) at 50% of IP presented a positive and small to moderate correlation with the PCS (r = 0.43, p = 0.047). The nBR and its associated psychophysical measures can be considered a sufficiently reliable test to assess the trigeminal nociceptive function. On the other hand, it seems not associated with psychological factors in healthy participants.